Sirt7 inhibits Sirt1-mediated activation of Suv39h1. Issue 12 (18th June 2018) - Kumari, Poonam; Popescu, Daniela; Yue, Shijing; Bober, Eva; Ianni, Alessandro; Braun, Thomas
ABSTRACT: Sirtuins regulate a variety of cellular processes through protein deacetylation. The best-known member of mammalian sirtuin family, Sirt1, plays important roles in the maintenance of cellular homeostasis by regulating cell metabolism, differentiation and stress responses, among others. Sirt1 activity requires tight regulation to meet specific cellular requirements, which is achieved at different levels and by specific mechanisms. Recently, a regulatory loop between Sirt1 and another sirtuin, Sirt7, was identified. Sirt7 inhibits Sirt1 autodeacetylation at K230 and activation thereby preventing Sirt1-mediated repression of adipocyte differentiation by inhibition of the PPARγ gene. Here, we extend the regulatory complexity of Sirt7-dependent restriction of Sirt1 activity by demonstrating that Sirt7 reduces activation of a previously described prominent Sirt1 target, the histone methyltransferase Suv39h1. We show that removal of the acetyl-group at K230 in Sirt1 due to the absence of Sirt7 leads to hyperactivation of Sirt1 and thereby to constantly increased activity of Suv39h1.